(untitled) (Research, Society and Development, 2020)
Introduction: brain head trauma (TBI) in childhood is a frequent cause of care in emergencies in Brazil and the world. Recognizing its severity early and offering adequate management markedly reduces morbidity and mortality. The World Health Organization (WHO) defines TBI as any aggression capable of causing anatomical damage or functional impairment of the scalp, skull, meninges or brain. Objectives: to trace the epidemiological profile of patients diagnosed with TBI in childhood. Methods: retrospective, quantitative and descriptive study based on the evaluation of the medical records of patients admitted to a medium-sized hospital in Serra Santa Catarina with high complexity in urgency and emergency in 2017 with a diagnosis of traumatic brain injury. The variables collected were: age, sex, month of occurrence, origin (city), accident site, accident mechanism, pre-hospital transport, Glasgow coma scale (ECG), type of injury, imaging exams, hospitalization in Intensive care unit (ICU), need for neurosurgery, need for inter-hospital transfer, length of hospital stay. Results: of the 50 medical records analyzed, there was a predominance of TBI in males (53%), aged between 6 and 10 years (33%), in April (18%), in the home environment (52%), for fall from own height (24%) and origin from Lages (62%). Most were classified as mild TBI (72%), underwent cranial computed tomography (80%) and received only clinical treatment (98%). The average length of hospital stay was 1 to 3 days (80%). Of these 2% of the patients died. Conclusions: the profile of these patients points to the need to implement preventive measures such as the removal of risk factors and the elaboration of a more up-to-date protocol for the care of patients who are victims of this disease.